Numerical simulation of heat transfer and flow of cooling air in triangular wavy fin channels - Ni, Ming-long; Chen, Ya-ping; Dong, Cong; Wu, Jia-feng (Journal of Central South University, 2014)
Numerical computation models of air cooling heat transfer and flow behaviors in triangular wavy fin channels (TWFC) were established with structural parameters of fins considered. The air side properties of heat transfer coefficient and pressure drop are displayed with variable structural parameters of fins and inlet velocities of cooling air. Within the range of simulation, TWFC has the best comprehensive performance when inlet velocity v in =4−10 m/s. Compared with those of straight fins, the simulation results reveal that the triangular wavy fin channels are of higher heat transfer performances especially with the fin structural parameters of fin-height F h =9.0 mm, fin-pitch F p =2.5−3.0 mm, fin-wavelength λ =14.0–17.5 mm and fin-wave-amplitude A =1.0–1.2 mm. The correlations of both heat transfer factor and friction factor are presented, and the deviations from the experimental measurements are within 20%.